Analysis of Four-tier Diagnostic Test on The Topic of Temperature and Heat in High School - Asih, Nur Fitri; Linuwih, Suharto; Fianti, Fianti (Universitas Negeri Semarang, 2022)
This study aims to analyze the feasibility of the four-tier diagnostic test items given to class XI high school students. This research is a quantitative descriptive study, which collects student answer sheets as data which is then analyzed for item selection, reliability, level of difficulty, discriminating power, distractor functioning, and readability test. This research was conducted on 30 students of class XI at SMA N 1 Slawi. The results concluded that in the selection of items from the 21 questions made, there were 16 items that were suitable for use and 5 items that were not suitable for use. In the reliability of the questions obtained by the reliability value of rcount of 0.760. In the level of difficulty, there are 5 questions in the easy category, 14 questions in the medium category, and 2 questions in the difficult category. In the differentiating power, the questions in the good category are 8 questions, the sufficient category is 8 questions, and the bad category is 5 questions. In the distractor function there are 10 questions whose distractors function well and 11 questions whose distractors do not function properly. Readability test questions according to student assessment questionnaires, four-tier diagnostic test questions are categorized as good to use.